Penguatan Nilai Budaya melalui Pelestarian Tradisi Bemeteng dalam Upacara Pernikahan di Desa Tebas Sungai - U. Sri Wulndari; Tomi Tomi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The Bemeteng tradition in Cempaka Hamlet, Tebas Sungai Village, Tebas District, Sambas Regency, is a form of community mutual cooperation in helping to organize wedding parties, especially for families who experience economic limitations. The implementation of the event involves extended family, neighbors, and local residents, while the main responsibility remains with the host. This tradition reflects the value of togetherness, social solidarity, and a culture of helping in community life. This study uses a qualitative method with a historical and sociocultural approach. Data was collected through observations, interviews with traditional leaders, religious leaders, and communities, and documentation studies. The analysis was carried out through data reduction, data presentation, and conclusion drawing to understand the dynamics and sustainability of the Bemeteng tradition during the period 2001–2025. The results of the study show that the implementation of Bemeteng began with a call from the community by the sarok about one week before the party. The Head of the Hamlet opened the activity by conveying the host's wishes, followed by the division of tasks such as collecting aid, kitchen work, and welcoming guests, then closed with prayers and a simple banquet. This tradition developed from a simple self-help pattern (2001–2010), underwent revitalization (2011–2019), restrictions during the pandemic (2020–2021), and has been active again since 2022 with digital support and cultural policies. The community views Bemeteng as an important heritage that strengthens unity and is in line with the values of deliberation and helping in Islamic teachings.